Patients with type 2 diabetes and elevated fibrosis‐4 are under‐referred to hepatology and have unrecognized hepatic decompensation. Issue 9 (15th June 2022) - Dunn, Winston; Song, Xing; Koestler, Devin; Grdinovac, Kristine; Al‐hihi, Eyad; Chen, John; Taylor, Ryan; Wilson, Jessica; Weinman, Steven A.
Abstract: Background and Aim: The American Association for the Study of Liver Diseases recommends a high index of suspicion for nonalcoholic steatohepatitis and advanced fibrosis in patients with type 2 diabetes (T2D) and an elevated fibrosis‐4 index (FIB‐4). We investigated the referral pattern of patients with T2D and FIB4 > 3.25 to the hepatology clinic and evaluated the clinical benefits to the patient. Methods: We included patients aged 18–80 years with T2D and a FIB4 score >3.25 who had visited the internal medicine, family medicine, endocrinology clinic from 01/01/2014–5/31/2019. The first time point of high‐risk FIB‐4 was identified as the baseline for time‐to‐event analysis. The patients were classified based on whether they had visited the hepatology clinic (referred vs not referred). Results: Of the 2174 patients, 290 (13.3%) were referred to the hepatology clinic, and 1884 (86.7%) were not referred. In multivariate analyses, the referred patients had a lower overall mortality risk (Hazard Ratio: 0.57; 95% CI: 0.38–87). Notably, the referred patients had the same rate of biochemical decompensation, as measured by progression to MELD ≥ 14, but a substantially higher rate of diagnosis in cirrhosis (27, 19–38) and cirrhosis complications, including ascites (2.9, 2.0–4.1), hepatic encephalopathy (99, 13–742), and liver cancer (14, 5–38). Conclusions: We found that patients with T2D and high‐risk FIB4 are associated with better overall survival after referral to a hepatology clinic. We speculate that the survival difference is due to the increased recognition of cirrhosis and cirrhosis complications in the referred populations.